Protocol data. - Konstanze Krueger (6750239) (2025)
Over recent decades, several predator species have returned to human-dominated landscapes in Europe, with wolves (Canis lupus) causing the most damage to livestock. In Germany, some ‘pioneer’ farmers started keeping guard dogs (Canis lupus familiaris) to protect their livestock, but these ‘pioneers’ faced opposition from a general public unfamiliar with methods of protecting against predators. To evaluate the use and management of guard dogs to protect various farm animal species against predators in rural areas frequently used by the public in Germany, we studied the behaviour of 113 guard dogs on farms across Germany that have frequent public contact. Two approaches were used: I) we observed guard dog proximity to and behaviour towards goats and horses with direct field observation, and II) we asked equine science and agriculture students trained in behaviour observations and official herd management commissioners to report their experiences of guard dogs during their initial visits to farms keeping various livestock species. These reports included observations of the dogs’ behaviour and information about the farm and dog management practices, and showed that guard dogs preferentially stay within 1 farm-animal body lengths of goats and horses. They adapted to a large variety of tasks and could protect various species. They displayed friendly behaviour towards the owners of the farms and known persons, and all behaviour categories towards farm animals and unfamiliar persons in the presence of the owner. They were dominant and watchful towards unknown persons and external dogs. The farmers’ training and socialising of their guard dogs appear to be successful, as older dogs, and large mixed-sex guard dog groups were consistently watchful against external individuals, but friendly towards farm personnel. In conclusion, guard dogs adapt well to guarding various species on German farms.